Períodos de interferência de plantas daninhas em culturas agrícolas - Foerster, Adriana Maria Lima (Brasil, 2022)
Weeds benefit from the process of competition with cultivated plants because of their high rusticity, resistance to pests and diseases, and high production of viable seeds. After weed interference is established on crops, the effects are irreversible, with no recovery in development and productivity even after removing the stress caused by the presence of weeds. This work aimed to gather information about the periods of weed interference in agricultural crops. The present work is a descriptive literature review that was carried out from research in national and international scientific articles, books, theses and dissertations of higher education in Portuguese and English that were published between the years 2011 and 2021, and publications prior to this period. All researched material was read and then selected according to their relevance to this review. Weeds compete directly with agricultural crops for common resources such as water, light, nutrients, space and the interference of these species in crops occurs in three periods; total period of interference prevention (PTPI), period before interference (PAI) and critical period of interference prevention (PCPI). Furthermore, these periods of weed interference in crops vary from region to region, vary between different agricultural crops and between cultivars of the same agricultural crop.